Getting more for less: can forensic tools for Australian wildlife enforcement support international compliance efforts?. Issue 4 (4th July 2019) - Ciavaglia, Sherryn; Dridan, Hannah; Linacre, Adrian
Abstract: Creating a robust set of hypervariable genetic markers for a species to assist forensic investigations regarding individualization and geographic assignment is both time and resource intensive. Yet, benefit can be maximized if the marker set has applicability in other closely related species of regulatory significance. We report a pilot study in which 24 short tandem repeat (STR) loci, developed to assist forensic investigations involving the Australian carpet python ( Morelia spilota ), have been assayed in six Australian and six Australasian python species of forensic and regulatory significance to investigate their utility in a much wider range of criminal investigations involving Australasian pythons. Eight of the 12 species showed amplification success at ten or more loci, indicating great potential for forensic investigations of Australasian python species without the requirement of further expensive marker characterization. A potential multiplex marker set is suggested for laboratories that are likely to encounter many of these species in forensic investigations. The results lay the foundation for wider application of effective regulatory and investigative tools, relevant to a large range of Australasian pythons of forensic significance.